Sustainable fisheries analysis with empowerment of local wisdom in Pasaman Barat District, West Sumatra, Indonesia - Parsaulian Baginda; Irianto Agus; Aimon Hasdi (BIO Web of Conferences, 2023)
Fish farming has become a commercial business, but the evidence so far is that progress has not been fully relied upon to boost the economy. The fisheries sub-sector, especially freshwater aquaculture, is based on the people’s economy, which can strive to survive and still be able to contribute to the economy by strengthening cultural assets in the form of local wisdom. This research aims to investigate the implementation of sustainable fisheries development based on the application of local wisdom to achieve sustainable fisheries in West Pasaman Regency, West Sumatra Province, Indonesia. This study used a mixed-methods model approach. The survey was conducted by distributing questionnaires to the respondents from aquaculture fishers’ households. The main findings of this study are sustainability and sustainable development are complex things where this can be achieved through an economic, ecological and social system where the pillars of economy and ecology are also need to consider social pillars including culture and institutions. To achieve sustainability, the scenario is built so that aquaculture activities in freshwater waters can be sustainable to achieve financial well-being, ecological sustainability in the form of availability of freshwater fish stocks and sustainability of local wisdom.